Electromagnetic Metal Forming for Advanced Processing Technologies - Batygin, Yuriy (Materials Forming, Machining and Tribology, 2018)
This book focuses on the new direction of magnetic pulsed metal working by attraction of sheet metals. In the first part, the authors focus on the magnetic pulsed pressure for forming of inner angles in the sheet metals. Part 2 of the book presents the magnetic pulsed attraction of thin-walled metals. In the third and last part, the authors present the practical realization of external restoring the dents on the car bodies by electromagnetic metal forming attraction.